2018
DOI: 10.1590/1809-4430-eng.agric.v38n4p526-535/2018
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Cattle Biogas Usage in Microturbines for Energy Generation and Thermal Exploitation

Abstract: The increase in confined cattle breeding reflects the modernization and automation of farming, which has significantly intensified in recent years and caused an increase in the energy demand of rural properties. This study investigated the use of biogas generated from dairy cattle manure confined in gas microturbines on a farm to generate electricity and the energy use of exhaust gases. At the end of the study, 6,195 to 16,077 kWh month-1 of electricity was obtained, which corresponds to 43.3% of the property'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…At the same time, very low emission of pollutants and noise level allow their use in virtually every facility. Microturbines can be supplied by different types of fuel, e.g., dairy cattle biogas [122], syngas [123] and biofuels [124].…”
Section: Gas Microturbinesmentioning
confidence: 99%
“…At the same time, very low emission of pollutants and noise level allow their use in virtually every facility. Microturbines can be supplied by different types of fuel, e.g., dairy cattle biogas [122], syngas [123] and biofuels [124].…”
Section: Gas Microturbinesmentioning
confidence: 99%
“…on the other hand, as noted in [20], the lowest costs for processing cow manure are provided during anaerobic digestion, and when selling energy from exhaust gases to a farm, one can get from 6.8 to 13.6 m 3 /day of warm water [21]. in [22], it was shown that biogas release from manure is 450 m 3 /t Vs, which is significantly less compared to biogas release during the fermentation of food waste (660 m 3 /t Vs).…”
mentioning
confidence: 99%
“…5 the condition is satisfied for a given accuracy of the result of the problem solving, i.е. |- 21 on the basis of the research conducted the following results were obtained:  the maximum release of biomethane for the pe-the maximum release of biomethane for the periodic loading of the substrate is determined, which is 14.3 l/kg DoM at 1.2% of the flour con-tent in the substrate; 20.9 l/kg DoM at 2.3%; 19.2 l/kg DoM at 5.6%; adding 10.6% of flour to the substrate causes the fermentation to stop;  a new model of biomethane release was developed during the fermentation of cow manure with the addition of flour-based newton polynomial of the second order and a new approach was developed for optimizing fermentation of cow manure with the addition of flour based on the use of the dichotomy method;  an optimal content of flour in the substrate is determined for the gradual loading of the met hane tank, that is 3,7%;  the recommendations on the rational content of flour in the substrate within the limits of 2.3-4.2% were substantiated, within these limits the biomethane release during the fermentation of the mixture of cow manure and flour is increased by 1.5 times.…”
mentioning
confidence: 99%